The Correlation Between Vocabulary Mastery and Speaking Ability of The First year Students of Senior High School - Indra, Rafiq Al; Eliwarti, Eliwarti; Syarfi, M. (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The Objective of this research is to find out the significant correlation between the vocabulary mastery and the speaking ability of the first year students of SMAN 10 Pekanbaru. The sample of this research was class X IPS 2, which consisted of 33 students. The data were collected using two kinds of test; namely, a vocabulary test and a speaking test. The results of this research showed that the first year students of SMAN 10 Pekanbaru got fair and poor level with the average score of 60.03 in vocabulary and 65.81 in speaking test which are considered as in poor Level. The results of this research proved that there was a positive correlation between the vocabulary mastery and the speaking ability of SMAN 10 Pekanbaru. The Rxy distribution of the coefficient correlation was 0.830. It means that there was a very strong correlation between these two variables. Therefore, it can be concluded that the vocabulary mastery has a strong and significant correlation with the speaking ability.